2021
DOI: 10.3233/ip-200269
|View full text |Cite
|
Sign up to set email alerts
|

Incorporating agile practices in public sector IT management: A nudge toward adaptive governance

Abstract: Public sector organizations are moving from digitalization toward digital transformation. However, this fast-paced and fundamental transformation can be difficult to manage with traditional approaches. One solution is the application of agile methods and adaptive governance. Currently, it is not clear whether the agile mindset can be successfully adopted by public sector organizations, which value stability over agility. To provide a much-needed example of how the agile approach can be introduced in the contex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(37 citation statements)
references
References 50 publications
0
36
0
1
Order By: Relevance
“…It resembles former management concepts such as lean management or total quality management and is linked to the resource-and capability-based view of organisations (Coffin & Tang, 2023;Harraf et al, 2015;Irfan et al, 2019). In general, a wide range of factors, perspectives, and elements seem to drive OA and describe the essence of an agile organisation (Franco et al, 2022): As a result, a consistent conceptualisation of the term is lacking (Walter, 2021;Ylinen, 2021).…”
Section: State Of Research -Agile Governmentmentioning
confidence: 99%
“…It resembles former management concepts such as lean management or total quality management and is linked to the resource-and capability-based view of organisations (Coffin & Tang, 2023;Harraf et al, 2015;Irfan et al, 2019). In general, a wide range of factors, perspectives, and elements seem to drive OA and describe the essence of an agile organisation (Franco et al, 2022): As a result, a consistent conceptualisation of the term is lacking (Walter, 2021;Ylinen, 2021).…”
Section: State Of Research -Agile Governmentmentioning
confidence: 99%
“…Information technology is a reality of our days, and the future means digitalization, sothe public sector cannot be absent from this natural evolution of things (Crîșmariu (Șomîtcă) & Șomîtcă, 2021). Public sector organizations are moving from digitalization toward digital transformation (Ylinen, 2021). In addition to the changes that occurred due to the industrial revolution, the Covid-19 pandemic that occurred in 2019 also required public sector organizations to be able to carry out public services online or remotely.…”
Section: F Adaptivementioning
confidence: 99%
“…The West Java Provincial Government started the digital government process in 2008, which was marked by the achievement of the West Java Provincial Government winning the Indonesian E-Government Ranking Award at the provincial level, awarded by the Ministry of Communication and Information. The digital transformation process of the public sector in West Java is still ongoing because the total digital transformation process is not an easy thing to do in a government whose large organization still implements a conventional government system (Ylinen, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Research conducted by Halim et al (2021) on the implementation of agile governance principles through the Pikobar application created and operated by Jabar Digital Service found that the principles of agile governance proposed by (Luna et al, 2015) were applied to the operation of the Pikobar application, namely based on quick wins, systematic and adaptive approach, and simple design and continuous refinement. Research on digital transformation in the public sector using agile methods has been conducted in developed countries (McBride et al, 2021;Sullivan et al, 2021;Ylinen, 2021). However, there are certainly differences between one country and another in terms of culture, economy, law, and social traditions, so the digital transformation process in the public sector carried out in an agile manner may be different from other countries.…”
Section: Introductionmentioning
confidence: 99%